Is apomixis a key to future seed production? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Apomictic plants are generally little known, although they are common in developing countries and have a biological characteristic which could be used to improve agricultural production: they reproduce even though they have only the female...